Institutional voids and the role of civil society: the case of global finance - Anheier, Helmut K. (Global policy, 2014)
Globalizing policy fields can contain institutional voids in which effective regulatory frameworks and the corrective counterbalance of civil society are equally absent. With the inherently incomplete regulation of global finance on the one hand and the evident dearth of civil society institutions on the other, a central governance question emerges: under what conditions could civil society help to recapture the financial system by embedding it in a wider social and economic policy, and thereby reversing the erosion of confidence in market capitalism and liberal democracy? For this purpose, this article proposes the systematic development of a transnational civil society infrastructure in terms of organizational capacity and expertise for accountability enforcement, policy review, performance oversight and advocacy. The goal of this infrastructure is to fill the institutional void and form a counterveiling force against the unchecked might of global finance.
First published: 25 October 2013
Gesehen am 07.10.2020